Receipt of Posthospitalization Care Training Among Medicare Beneficiaries’ Family Caregivers - Burgdorf, Julia G. (JAMA Netw Open, 2021)
IMPORTANCE: Medicare conditions of participation require hospitals to provide training to family and unpaid caregivers when their support is necessary to enact the postdischarge care plan. However, caregivers often report feeling unprepared for this role. OBJECTIVE: To describe the characteristics of caregivers who assist with posthospitalization care transitions and assess the prevalence of and factors associated with receipt of adequate transitional care training. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study analyzed data from the 2017 National Health and Aging Trends Study and its linked National Study of Caregiving, surveys of Medicare beneficiaries and their family and unpaid caregivers. The present study included family caregivers for community-living Medicare beneficiaries 65 years or older with disabilities. Data analysis was performed from June to September 2020. MAIN OUTCOMES AND MEASURES: Characteristics of family caregivers by whether they assisted during a posthospitalization care transition in the year preceding the survey interview. Unweighted frequencies and weighted percentages, as well as the results of weighted Pearson and Wald tests for differences between groups, are reported. Receipt of the training needed to manage the older adult’s posthospitalization care transition (hereafter referred to as adequate transitional care training) as a function of individual caregiver characteristics was modeled using multivariable, weighted logistic regression. RESULTS: Of 1905 family caregivers, 618 (58.9%) were 60 years or older, 1288 (63.8%) were female, and 796 (41.7%) assisted with a posthospitalization care transition. Those who assisted with a posthospitalization care transition were more likely to report experiencing financial (154 [18.3%] vs 123 [10.1%]; P < .001), emotional (344 [41.3%] vs 342 [31.1%]; P < .001), and physical (200 [22.2%] vs 170 [14.6%]; P = .001) difficulty associated with caregiving. Among caregivers who assisted during a posthospitalization care transition, 490 (59.1%) reported receiving adequate transitional care training. Caregivers were less likely to report receiving adequate training if they assisted an older adult who was female (316 [62.3%] vs 227 [73.2%]; P = .02), Black (163 [14.0%] vs 121 [19.8%]; P = .02), or enrolled in Medicaid (127 [21.2%] vs 90 [31.9%]; P = .01). After adjusting for older adult characteristics, caregivers were half as likely to report receiving adequate training if they were Black (adjusted odds ratio [aOR], 0.52; 95% CI, 0.31-0.89) or experienced financial difficulty (aOR, 0.50; 95% CI, 0.31-0.81). Caregivers were more than twice as likely to report receiving adequate training if they were female (aOR, 2.44; 95% CI, 1.65-3.61) or spoke with the older adult’s clinician about his or her care in the past year sometimes or often vs never (aOR, 1.93; 95% CI, 1.19-3.12). CONCLUSIONS AND RELEVANCE: In this cross-sectional study, caregivers were less likely to receive adequate transitional care training if they were Black; experienced financial difficulty; or cared for a Black, female, or Medicaid-enrolled older adult. These findings suggest that changes to the discharge process, such as using standardized caregiver assessments, may be necessary to ensure equitable support of family caregivers.